Etika dan Kebijakan Lingkungan dalam Pengelolaan Perkotaan - Thalib, Heru Z; Kumaji, Syam S; Hamidun, Marini Susanti; Panai, Abdul Haris; Rahim, Sukirman; Yusuf, Daud (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
This research examines ethics and environmental policies in urban management across various countries. The study shows that rapid urbanization and environmental issues, such as clean water shortages and poor sanitation, have a negative impact on public health. The author identifies knowledge gaps in the integration of interdisciplinary approaches to achieve holistic sustainability solutions. The article highlights various regenerative approaches in environmental management, including circular economy and regenerative tourism, as solutions to address environmental and social challenges. The findings of this research indicate that active participation of local communities and improvements in infrastructure, such as clean water and sanitation, significantly enhance public health and environmental sustainability. The implications of this research emphasize the importance of cross-sector collaboration and regenerative approaches in supporting urban sustainability and reducing environmental and social risks